Molecular insights into HSD10 disease: impact of SDR5C1 mutations on the human mitochondrial RNase P complex. Issue 10 (29th April 2015) - Vilardo, Elisa; Rossmanith, Walter
Abstract: SDR5C1 is an amino and fatty acid dehydrogenase/reductase, moonlighting as a component of human mitochondrial RNase P, which is the enzyme removing 5′-extensions of tRNAs, an early and crucial step in tRNA maturation. Moreover, a subcomplex of mitochondrial RNase P catalyzes the N 1 -methylation of purines at position 9, a modification found in most mitochondrial tRNAs and thought to stabilize their structure. Missense mutations in SDR5C1 cause a disease characterized by progressive neurodegeneration and cardiomyopathy, called HSD10 disease. We have investigated the effect of selected mutations on SDR5C1's functions. We show that pathogenic mutations impair SDR5C1-dependent dehydrogenation, tRNA processing and methylation. Some mutations disrupt the homotetramerization of SDR5C1 and/or impair its interaction with TRMT10C, the methyltransferase subunit of the mitochondrial RNase P complex. We propose that the structural and functional alterations of SDR5C1 impair mitochondrial RNA processing and modification, leading to the mitochondrial dysfunction observed in HSD10 patients.